2017
DOI: 10.1155/2017/5673214
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State FTIR Spectroscopic Study of Two Binary Mixtures: Cefepime-Metronidazole and Cefoperazone-Sulbactam

Abstract: The structural information of the pharmaceuticals and insights on the modes of molecular interactions are very important aspects in drug development. In this work, two cephalosporins and antimicrobial combinations, cefepime-metronidazole and cefoperazone-sulbactam, were studied in the solid state using FTIR spectroscopy for the first time. Quantitation of the studied drugs and their binary mixtures was performed by integrating the peak areas of the characteristic well-resolved bands:υ(C=O) band at 1773 cm−1for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The major decomposition stage indicates the breakdown of covalent bonds and modified chemical configurations, with the greatest weight loss about 400 °C. Tan et al [ 90 ] reported that the oxidative stability of vegetable oils showed similar results and that the oils that contained high proportions of free fatty acids were more liable to oxidation; the authors determined that liberated FAs show less constant oxidation than FAs bound to glycerol molecules. Fatty acids with elongated carbon chains are more constant as a result of heating degradation than the short-chain FAs attributed to increasing intermolecular dispersal powers [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The major decomposition stage indicates the breakdown of covalent bonds and modified chemical configurations, with the greatest weight loss about 400 °C. Tan et al [ 90 ] reported that the oxidative stability of vegetable oils showed similar results and that the oils that contained high proportions of free fatty acids were more liable to oxidation; the authors determined that liberated FAs show less constant oxidation than FAs bound to glycerol molecules. Fatty acids with elongated carbon chains are more constant as a result of heating degradation than the short-chain FAs attributed to increasing intermolecular dispersal powers [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 b, which details the wavelength range between 2000 and 500 cm −1 , shows the positions of the absorbance peaks more clearly. Thus, Figure 6 a,b reveals MET characteristics like OH (alcohol) stretching band which appears at 3201 cm −1 , C–H (aromatic) stretching at 3099 cm −1 , C–NO 2 and N–O stretching at 1535 cm −1 , CH 2 scissoring at 1471 cm −1 , C–OH and C–O stretching at 1047 cm −1 and C–NO 2 and C–N stretching at 825 cm −1 [ 23 , 24 , 25 ]. In Figure 6 b, the spectrum of PCL-5% nHAP-20% MET and the specific bands of MET can be highlighted more easily.…”
Section: Resultsmentioning
confidence: 99%
“…In curves obtained for powder mixtures as well as for printlets, two crystallization effects were observed at about 129 • C (the same for the mixture and the sintered sample), 42 • C (for the mixture) and 27 • C (for the sintered sample). From the comparison of crystallization enthalpies of PA12 and Met with those obtained from the mixture and the sintered sample, it could be assumed that the effect at 129 In ATR-IR spectra, Met was easily identified by the intensive bands at 3209 cm −1 (from O-H stretching vibrations), 3100 cm −1 (from C-H stretching vibrations), 1534 cm −1 (from -NO2 asymmetric stretching vibrations), 1472 cm −1 and 1427 cm −1 (from C-H deformation vibrations), 1367 cm −1 (from -NO2 symmetric stretching vibrations), 1186 cm −1 (from C-O stretching vibrations) and 1073 cm −1 (from the ring breathing mode) [47].…”
Section: The Effect Of Sintering On the Phase Transitions Of Printlet...mentioning
confidence: 99%
“…In the spectra of both mixtures, mainly Met bands were observed as well as two characteristic bands at 2971 cm −1 (Figure 6a) and 1637 cm −1 (Figure 6b) from PA12. In ATR-IR spectra, Met was easily identified by the intensive bands at 3209 cm −1 (from O-H stretching vibrations), 3100 cm −1 (from C-H stretching vibrations), 1534 cm −1 (from -NO 2 asymmetric stretching vibrations), 1472 cm −1 and 1427 cm −1 (from C-H deformation vibrations), 1367 cm −1 (from -NO 2 symmetric stretching vibrations), 1186 cm −1 (from C-O stretching vibrations) and 1073 cm −1 (from the ring breathing mode) [47].…”
Section: The Effect Of Sintering On the Phase Transitions Of Printlet...mentioning
confidence: 99%